Heart-type fatty acid binding protein levels in elderly diabetics without known cardiovascular disease - Beysel S (Dove Medical Press, 2017)
Selvihan Beysel,1,2 Muhammed Kizilgul,3 Mustafa Ozbek,4 Mustafa Caliskan,5 Seyfullah Kan,6 Mahmut Apaydin,7 Ozgur Ozcelik,8 Erman Cakal4 1Department of Endocrinology and Metabolism, Eskisehir State Hospital, Eskisehir, 2Department of Medical Biology, Baskent University, Ankara, 3Department of Endocrinology and Metabolism, Kilis State Hospital, Kilis, 4Department of Endocrinology and Metabolism, Diskapi Yildirim Beyazit Teaching and Research Hospital, Ankara, 5Department of Endocrinology and Metabolism, Düzce Ataturk State Hospital, Duzce, 6Department of Endocrinology and Metabolism, Denizli State Hospital, Denizlim, 7Department of Endocrinology and Metabolism, Yozgat State Hospital, Yozgat, 8Department of Endocrinology and Metabolism, Igdir State Hospital, Igdir, Turkey Background: Cardiovascular disease (CVD) is reported to be higher in elderly diabetics. Serum heart-type fatty acid binding protein (H-FABP) is a serum marker of myocardial ischemia. We aimed to investigate the association between serum H-FABP level and conventional cardiovascular risk factors, inflammatory markers and subclinical atherosclerosis in elderly diabetics without overt CVD. Patients and methods: A total of 50 elderly diabetic patients without overt CVD and 30 age-, sex- and body mass index (BMI)-matched healthy controls were enrolled. Anthropometric and biochemical parameters, serum H-FABP, high-sensitivity C-reactive protein (hs-CRP), fibrinogen and carotid intima-media thickness (CIMT) were measured. Logistic regression analyses (adjustments for age, sex, hypertension, smoking, diabetes, BMI, blood pressure, lipid, blood glucose, hemoglobin A1c, hs-CRP and fibrinogen) were performed to evaluate the association between H-FABP and cardiovascular risk factors and atherosclerosis indices. Results: Serum fibrinogen (421.50±85.52 mg/dL vs 319.17±30.77 mg/dL, p=0.023), CIMT (0.70±0.12 mm vs 0.59±0.06 mm, p<0.001) and hs-CRP (5.72±4.50 mg/dL vs 1.60±0.72 mg/dL, p<0.001) were significantly higher in diabetic patients than controls. The mean serum H-FABP level did not differ between groups (1571.79±604.60 ng/mL vs 1500.25±463.35 ng/mL, p=0.905). H-FABP was positively correlated with fibrinogen (r2=0.473, p<0.001), hs-CRP (r2=0.323, p=0.003) and CIMT (r2=0.467, p<0.001). After full adjustments, the serum H-FABP level was independently associated with an increase in the fibrinogen level (odds ratio [OR] =4.21, 95% confidence level [CI] =1.49–11.90). Conclusion: Serum H-FABP was similar in the elderly diabetic patients without known CVD when compared with the nondiabetic control group. H-FABP does not possess a high diagnostic value as a cardiovascular marker when used alone; however, it may add supplementary information in patients with a high fibrinogen level. Keywords: H-FABP, elderly diabetics, cardiovascular risk